ANALYSIS OF ELEMENTARY SCHOOL EDUCATION INFRASTRUCTURE FULFILLMENT IN CIBEUNYING KIDUL DISTRICT: A CASE STUDY OF PUBLIC ELEMENTARY SCHOOL 004 CICADAS AWIGOMBONG, BANDUNG CITY - Nurulhuda, Encep (Journal of Development and Integrated Engineering, 2023)
The current availability of land to meet the needs of educational unit support infrastructure is one of the problems that often arises amidst the difficulty of land availability in accordance with its designation. Cibeunying Kidul District is one of the sub-districts in the city of Bandung which has a fairly large population with housing that is in the high density category. The purpose of this research is to find out the existing condition of fulfilling the scale of education facility services and fulfilling the standard infrastructure that must be provided in basic education units as well as adjustments to future conditions in the implementation of education in Cibeunying Kidul District in 2023 and the achievement of each student from home to school in accordance with the implementation of the zoning system. the method used is to conduct a literature study by including case studies as a measuring tool in finding answers to the problems found. The results showed that of the 16 elementary schools in Cibeunying Kidul District, 53% of the availability of classroom infrastructure was still insufficient compared to the number of students in each school, 47% were sufficient. If you look at the development of the population in the next 6 or 7 to 12 years, a large enough additional land is needed to provide classroom infrastructure in the future. Other infrastructure such as the teacher's room, principal's room, library, toilets, prayer room, and ceremonial and sports fields which were seen in one of the case study schools showed that even though the achievements were in accordance with the stipulated zoning system, the fulfillment of other infrastructure was no longer possible to develop. in accordance with the number of existing students, so that in addition to providing new land, setting the time for learning, the new solution is to change the learning method to a blended learning system with digital learning media which will not require a large enough space requirement as currently determined standards.